Uncertainty avoidance and security threats, tourist ethnocentrism, and cultural intelligence as determinants of foreign travel destination selection - Spalević, Žaklina; Zdravković, Stefan; Milojković, Hristina (Hotel and Tourism Management, 2026)
Purpose – The development of information systems and transportation networks has enabled greater human mobility and simplified the organization of both business and tourist trips abroad. The aim is to test the impact of uncertainty avoidance and security threats, tourist ethnocentrism, and cultural intelligence on the selection of foreign tourist destinations. Methodology – The research was implemented in the Republic of Serbia at the end of 2024 using a questionnaire with the participation of 608 respondents, and their responses were analyzed using the software SmartPLS 4. Findings – The analysis revealed that uncertainty avoidance, security threats, and tourist ethnocentrism exert a negative influence, while cultural intelligence exerts a positive influence on respondents’ decisions regarding the selection of foreign tourist destinations. The degree of uncertainty avoidance, security threats, and tourist ethnocentrism was higher among respondents with lower levels of education and monthly income, whereas the degree of cultural intelligence was more pronounced among respondents with higher levels of education and income. Implications – The implications lie in the implementation of a holistic approach when conceptualizing the model and providing relevant insights for the formulation of strategies in the field of tourism.